Potential Therapeutic Effects of Exogenous Ketone Supplementation for Type 2 Diabetes: A Review - Walsh, Jeremy J.; Myette-Côté, Étienne; Neudorf, Helena; Little, Jonathan P. (Current Pharmaceutical Design, 2020)
Type 2 diabetes (T2D) is among the most prevalent non-communicable lifestyle diseases. We propose that overnutrition and low levels of physical activity can contribute to a vicious cycle of hyperglycemia, inflammation and oxidative stress, insulin resistance, and pancreatic β-cell dysfunction. The pathophysiological manifestations of T2D have a particular impact on the vasculature and individuals with T2D are at high risk of cardiovascular disease. Targeting aspects of the vicious cycle represent therapeutic approaches for improving T2D and protecting against cardiovascular complications. The recent advent of exogenous oral ketone supplements represents a novel, non-pharmacological approach to improving T2D pathophysiology and potentially protecting against cardiovascular disease risk. Herein, we review the emerging literature regarding the effects of exogenous ketone supplementation on metabolic control, inflammation, oxidative stress, and cardiovascular function in humans and highlight the potential application for breaking the vicious cycle of T2D pathophysiology.
Keywords: diabetes